2018
DOI: 10.3389/fmicb.2018.02518
|View full text |Cite
|
Sign up to set email alerts
|

SakA and MpkC Stress MAPKs Show Opposite and Common Functions During Stress Responses and Development in Aspergillus nidulans

Abstract: Stress activated MAP kinases (SAPKs) of the Hog1/Sty1/p38 family are specialized in transducing stress signals. In contrast to what is seen in animal cells, very few fungal species contain more than one SAPK. Aspergillus nidulans and other Aspergilli contain two SAPKs called SakA/HogA and MpkC. We have shown that SakA is essential for conidia to maintain their viability and to survive high H2O2 concentrations. H2O2 induces SakA nuclear accumulation and its interaction with transcription factor AtfA. Although S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 46 publications
0
41
0
1
Order By: Relevance
“…This hypothesis is corroborated by the fact that A. nidulans SakA and MpkC not only physically interact, but also show opposite and common functions during stress responses and development (51, 52).…”
Section: Discussionmentioning
confidence: 76%
“…This hypothesis is corroborated by the fact that A. nidulans SakA and MpkC not only physically interact, but also show opposite and common functions during stress responses and development (51, 52).…”
Section: Discussionmentioning
confidence: 76%
“…There is strong evidence showing that ROS regulate fungal development (Hansberg and Aguirre, 1990;Lara-Ortiz et al, 2003;Aguirre et al, 2005;Cano-Dominguez et al, 2008Lara-Rojas et al, 2011;Mendoza-Martinez et al, 2017;Garrido-Bazan et al, 2018). We have shown that mitochondrial division is critically associated to fungal development and ROS production and that mitochondrial division is in turn regulated by ROS.…”
Section: Mitochondrial Fission Is Connected To Development and Inducementioning
confidence: 76%
“…In one approach, we have used the filamentous fungi Aspergillus nidulans to study the mechanisms by which cells perceive and respond to external ROS. In this and other fungi, the SakA-MpkC stress MAPK pathway plays crucial roles in responding to multiple types of stress, including oxidative stress (Kawasaki et al, 2002;Lara-Rojas et al, 2011;Garrido-Bazan et al, 2018). During the course of that work, we found that the MAPKAP-kinase SrkA is part of this pathway and that in response to external H 2 O 2 it translocates from the cytoplasm to either the nucleus or the mitochondria, depending on the presence of the upstream MAPK SakA.…”
Section: Introductionmentioning
confidence: 85%
“…An important player in red-light regulation and stress signaling in A. nidulans is the HOG MAP kinase SakA (38, 61, 67). There is also evidence for a link between blue-light signaling and the transcriptional and posttranslational regulation of the MAP kinase Tmk3 in Trichoderma atroviride and in N.…”
Section: Discussionmentioning
confidence: 99%